A new species of iguana Brachylophus Cuvier 1829 (Sauria: Iguania: Iguanidae) from Gau Island, Fiji Islands - Fisher, Robert N.; Niukula, Jone; Watling, Dick; Harlow, Peter S. (Zootaxa, 2017)
The south Pacific iguanas (Brachylophus) currently have three recognized living species in Fiji.  Recent surveys have uncovered more specific variation (morphological and genetic) within the genus and have better defined the geographic ranges of the named species.  One of these recent discoveries is a strikingly different iguana from all other island populations in Fiji which is restricted to Gau Island of the Lomaiviti Province.  Gau is the fifth largest island in Fiji and maintains excellent upland forests in the higher elevations.  We describe this population from Gau Island as a new species, Brachylophus gau sp. nov., in recognition of its type locality.